Reflections of some manifestation of globalization on national sovereignty - Timrez, Ismail; Mallem, Youcef (Journal of Human Sciences, 2023)
Sovereignty is one of the most important foundations on which the state is based , but it faced some danger with the appearance of some recent developments on the international scene that had a clear impact on the state’s imposition of its sovereignty on its land.Globalization and its methods were among the most important manifestations that have emerged in recent times and had the greatest and most effective impact on sovereignty. International cooperation was one of the most important developments that occurred, as it focused on ways of cooperation and assistance between countries and reducing borders and working to remove them, in addition to multinational companies that increased Its activity is due to globalization until it has become its most important method. Accordingly, how and to what extent has globalization affected national sovereignty?